Potensi Maggot Sebagai Alternatif Pengelolaan Sampah Organik Limbah Rumah Tangga Di Desa Purwodadi Pasuruan - Aldian Syafputra Pratama; Taslim Sjah (Lembaga Bale Literasi, 2024)
Organic waste is a problem that is difficult to overcome if you just bury it or let it rot because it will have an impact on pollution in the form of an unpleasant odor. This research aims to examine the potential of black soldier fly (maggot) larvae in decomposing household organic waste and to examine products produced by black soldier fly (maggot) larvae that are useful and have economic value. This research is a qualitative descriptive research using quantitative and qualitative data types sourced from primary data and secondary data. The results and discussion show that maggots are an effective alternative for processing leftover household organic waste because maggots are able to break down 5 to 10 kg of waste per day. Apart from that, maggots have value from an economic perspective and can increase income.